Approaches to Reducing the Number of Claims Regarding Drinking Water Provision in Moquegua, 2019 - Lizarme Rivas, Angélica (2023)
In Peru, drinking water is administered by Sanitation Service Providing Entities (EPS by their Spanish initials). Each of these interacts with its users, and various problems and claims have emerged in relation to the service they provide. This quantitative study analyzes the reasons behind the number of claims against EPS Moquegua S.A. The purpose of this research is to determine the required approach to the reduction in claim numbers regarding drinking water provision in Moquegua in 2019. This study is applied, descriptive and explanatory-causal. It has a cross-sectional causal design. Its universe was 22,400 users from Moquegua, while the statistical sample consisted of 378 users. The data collection and research variable measurement instruments were a questionnaire-survey and documentary information from EPS Moquegua. The results obtained and validated through the mean of the sample distribution showed and determined that the appropriate management strategies that favorably influence the reduction in the number of complaints are: "Equipment and support" and the "Perception study", a tool that reflects the customers' perceptions of the service. The study results show that 66.5% of claims is due to measurement errors. From the moment they were first implemented, management strategies improved the service and the number of claims decreased from 3,074 to 2,955 in 2019.